Compact and multiband metamaterial hairpin-line bandpass filters - Mohd. Sobri, Muhammad Akram (2018)
In RF and microwave field, the bandpass filters are very important in communication systems. Bandpass filters are used as frequency selective devices in many RF and microwave applications such as transmitter and receiver. In recent years, a new type of artificial materials called as metamaterials have attracted the attention of many researchers. Metamaterials have a wide range of potential uses in communication areas such as optical and RF design. The metamaterial is a material engineered to have an electromagnetic property that is not found in nature. Thanks to the presence of these properties many researchers have using the metamaterial to produce the high performance and compact devices. The rapid development of microwave and millimeter wave in communication systems greatly stimulates the demand for high-performance bandpass filters with compact dimensions, low insertion loss, high attenuation in the stopband, low cost and multiband responses. In this project, the compact and multiband metamaterial hairpin bandpass filters have been proposed to reduce the size of the filter and to provide a multiband filter with less complex structure. The proposed bandpass filters were designed by using the complementary split ring resonator (CSRR) structure. The compact size was achieved with size reduction of 10% from the conventional hairpin filter. For the proposed multiband bandpass filter, two-band frequency responses were obtained at 3.5 and 5.5 GHz. Moreover, both of them have an insertion loss less than 1 dB and high attenuation at stopband.